Manajemen Hubungan Sekolah dengan Masyarakat dalam Penguatan Pendidikan Islam (JMPI: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to analyze the management of school-community relationships in strengthening Islamic Religious Education (PAI), with an emphasis on transforming the role of the community, reinforcing the value base, and developing participatory communication. This study is motivated by the limited involvement of the community, which is often formal and not yet optimally integrated into the educational process. The research employed a qualitative approach through a literature study, examining various relevant scholarly sources to achieve a comprehensive conceptual understanding. The findings indicate that the strengthening of PAI cannot be separated from the reorientation of the community as an active educational partner in shaping students' character. Furthermore, alignment of values between schools and the social environment is crucial to ensure successful internalization of Islamic values. In addition, participatory and dialogical communication has been shown to build trust and enhance the effectiveness of collaboration between the two parties. These findings emphasize that school-community relationships need to be managed systematically, not only in technical aspects but also in terms of values and social interactions. Consequently, the established partnership can make a significant contribution to creating an educational environment that supports the sustainable development of students’ religious character. Keywords: educational partnership, participatory communication, Islamic Religious Education, community role, value reinforcement